THE ROLE OF GOVERNMENT PROCUREMENT IN DEVELOPING A SUSTAINABILITY CULTURE WITHIN THE FURNITURE INDUSTRY - Lima, Clarissa Melo; da Costa, Tito Ricardo Vaz; Lima, João Batista Melo; Trigueiro Filho, Machidovel; da Silva Junior, Luiz Honorato; Oliveira, Cecília Leite; Campolino, Rafael Gonçalves; Gonçalez, Joaquim Carlos (Seven Editora, 2026)
This paper presents an overview of the furniture industry and the opportunities within the scope of sustainable government procurement. The objective of the study was to evaluate opportunities, threats, weaknesses, and strengths so that industries in this segment can engage responsibly in sustainable development. The research was conducted in the Federal District with furniture industries from the main Administrative Regions (AR). The techniques used included the application of questionnaires and the SWOT methodology. The study demonstrated that public procurement plays an important role in supporting micro and small enterprises so they can comply with environmental sustainability requirements.DOI: https://doi.org/10.56238/sevened2026.008-050